Aligned piezoelectric fibrous scaffolds for prevention of traumatic neuroma formation - Chen, Yujie; Gu, Xinyi; Zang, Huiran; Wang, Cai; Li, Guangxue (Frontiers in Bioengineering and Biotechnology, 2026)
PurposeTraumatic neuroma, a painful complication of peripheral nerve injury, arises from disorganized axonal regeneration and chronic inflammation. Existing treatments provide limited relief. This study aimed to evaluate the therapeutic potential of aligned piezoelectric poly (L-lactide) (PLLA) fibrous scaffolds in preventing neuroma formation by promoting nerve regeneration and mitigating inflammatory and pain-related responses.MethodsAligned PLLA fibrous scaffolds were fabricated using electrospinning and characterized for morphology and piezoelectricity. In vitro, Schwann cell proliferation, morphology, and expression of myelination-related genes (Mag, Mbp, Mpz) were assessed. In vivo, a rat sciatic nerve transection model was used to evaluate autotomy behavior, nerve regeneration, inflammatory and pain-related markers (TNF-α, IL-10, SP, c-Fos), and transcriptomic changes.ResultsPLLA scaffolds significantly promoted Schwann cell proliferation and upregulated myelination-related genes in vitro. In vivo, they reduced autotomy scores and suppressed the expression of inflammatory and nociceptive markers. Histological analyses demonstrated enhanced axonal regeneration and myelination, with greater NF200 and S100 expression, thicker myelin sheaths, and improved structural integrity. Transcriptome analysis revealed upregulation of neuroregenerative genes (e.g., Mag, Mpz, Sox10, Egr2) and anti-inflammatory cytokines (e.g., IL-10, TGF-β), alongside downregulation of proinflammatory and pain-associated genes (e.g., SP, c-Fos, Mmp9, Tnf-α).ConclusionAligned piezoelectric PLLA fibrous scaffolds facilitate functional nerve regeneration, promote remyelination, and attenuate neuropathic pain and inflammation. These findings suggest that such scaffolds offer a promising nanomedicine-based strategy for the prevention of traumatic neuroma following peripheral nerve injury.